2016
DOI: 10.1097/ijg.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Childhood Glaucoma

Abstract: Childhood glaucoma carries a substantial economic burden with the highest costs occurring in the first year after presentation. The greatest contributors to cost of illness are surgical interventions and examinations and anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Those with glaucoma-induced visual impairments generally suffer from decreased vision-related quality of life (including reduced vision-dependent mobility and increased incidence of falls) [6,7]. This places a substantial burden on medical care systems [8-10]. Glaucoma is often associated with a long and asymptomatic initial phase and usually progresses unnoticed until extensive and irreversible vision loss has occurred.…”
mentioning
confidence: 99%
“…Those with glaucoma-induced visual impairments generally suffer from decreased vision-related quality of life (including reduced vision-dependent mobility and increased incidence of falls) [6,7]. This places a substantial burden on medical care systems [8-10]. Glaucoma is often associated with a long and asymptomatic initial phase and usually progresses unnoticed until extensive and irreversible vision loss has occurred.…”
mentioning
confidence: 99%
“…They report a significant reduction in their vision related quality of life (VR QoL) and health related (HR) QoL compared with normally sighted individuals, and decreased functional visual ability as well as a substantial economic burden. 94,95 Predictors of poor final visual outcome in the childhood glaucoma's include the presence of nystagmus, anterior segment dysgenesis or early failed angle surgery. Whereas failed angle surgery and presence of media opacity predicted poor final IOP control.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found the direct costs are significant in the first years of the disease. 16 Blanco et al enrolled patients from 30 hospital eye services in five countries. They found the lens extraction was more expensive than the standard care.…”
Section: Discussionmentioning
confidence: 99%